Pengaruh Terapi Genggam Bola Karet terhadap Peningkatan Kekuatan Otot pada Pasien Stroke Non Hemoragik di RSUD Kardinah Kota Tegal - Salma Munifah; Ani Ratnaningsih; Eko Sistyawan; Imam Safii (NAJ Nursing Applied Journal, 2024)
Non hemorrhagic stroke is a disorder caused by ischemia, thrombosis, embolism, and narrowing of the lumen so that blood flows to the brain stops. This type of stroke can have an impact on various body functions including muscle weakness. Rubber ball grip exercises can stimulate movement in the hands for gripping function so that it can restore brain control over weakened upper extremity muscles. This study aimed to describe the application of rubber ball grip exercises to upper extremity muscle strength in non-hemorrhagic stroke patients. The research design used a case study approach. Data collection was carried out on May 30 - June 1 2023 at Kardinah Hospital, Tegal City with 2 patients having a medical diagnosis of non-hemorrhagic stroke. Both patients experienced an increase in upper extremity muscle strength. Patient 1 during 3 days of therapy experienced a change in muscle strength from 4 to 5. In patient 2 after 3 days of therapy experienced a change in muscle strength from 3 to 4.. The results showed that subject 1 experienced an increase in muscle strength from 4 to 5, subject II experienced an increase in muscle strength from 3 to 4. patients with non-hemorrhagic stroke are used to do rubber ball grip therapy for 10-15 minutes per day within 3 days to stimulate weak muscle strength.